‘Mutiara Mahkota: Tengku Abdullah al-Haj’ Won the National Book Award 2018 - Nur Laila, Afandi (2018)
Kuala Lumpur, 30 April - The outstanding achievement of Universiti Malaysia Pahang (UMP) in the field of publishing continues to shine as the book 'Mutiara Mahkota: Tengku Abdullah al-Haj' published by UMP Publisher won the National Book Awards 2018 (Best Public Books - Royal Biography Category) in conjunction with the Kuala Lumpur International Book Fair (KLIBF) 2018 recently.